Nutritional compositions, total phenolics, antioxidant capacities, and students’ knowledge level about plant-based meat items - Chen, Yu Wei (2023)
Plant-based meats (PBM) items are processed plant-based products intended to replicate the sensory characteristics of animal-based products. With increasing global health awareness, PBM items are gaining popularity owing to their superior nutritional and antioxidant characteristics, which make them potentially a healthier option than meat-based products. However, little is known about the nutritional and antioxidant information on ready-to-eat PBM items, particularly those marketed in Malaysia. Therefore, this study aims to determine the nutritional compositions (carbohydrate, protein, fat, fiber, ash and moisture) using proximal analyses and antioxidant properties (total phenolics content (TPC), total flavonoid content (TFC) and antioxidant capacities) using Folin-Ciocalteu, Aluminuium Chloride, DPPH and ABTS assays, for three PBM items: Kale Pizza (KP), Double Cheeseburger (DCB) and Spaghetti in Carbonara with Plant-Based Minced Meat (SC). One-way analysis of variance (ANOVA) and Tukey test were used to determine the significant differences of results at p <0.05 level, and Pearson correlation was performed to examine the association between antioxidant parameters. Also, a cross-sectional survey was conducted to assess the consumers’ knowledge of PBM items among Universiti Tunku Abdul Rahman (UTAR) undergraduate students. Questionnaires were distributed virtually to eligible participants throughout the data collection period. Based on the results, moisture (54–66%) constituted the largest proportion of all samples, followed by carbohydrates (28–33%), fat (3–6%), fiber (2–4%) and ash (1–3%), while protein (<l%) made up the least. KP and DCB had lower moisture content, higher ash, protein, fat and carbohydrate contents than SC. There were no significant differences in fiber content, TPC and TFC, while SC exhibited the lowest antioxidant capacity. Besides, TPC exhibited a strong association with antioxidant capacity (r = 0.94; r = 0.90), while TFC had a weak to-moderate association (r = 0.46; r = -0.31). Overall, UTAR undergraduates revealed a low knowledge level (37%), particularly in terms of nutritional knowledge of PBM items, highlighting the necessity of educational efforts to improve their understanding in this aspect